Archetypes of human cognition defined by time preference for reward and their brain correlates: An evolutionary trade-off approach - Cona, Giorgia; Koçillari, Loren; Palombit, Alessandro; Bertoldo, Alessandra; Maritan, Amos; Corbetta, Maurizio (NeuroImage (Orlando, Fla.), 2019)
Biological systems carry out multiple tasks in their lifetime, which, in the course of evolution, may lead to trade-offs. In fact phenotypes (different species, individuals within a species, circuits, bacteria, proteins, etc.) cannot be optimal at all tasks, and, according to Pareto optimality theory, lay into a well-defined geometrical distribution (polygons and/or polyhedrons) in the space of traits. The vertices of this distribution contain archetypes, namely phenotypes that are specialists at one of the tasks, whereas phenotypes toward the center of the geometrical distribution show average performance across tasks. We applied this theory to the variability of cognitive and behavioral scores measured in 1206 individuals from the Human Connectome Project. Among all possible combinations of pairs of traits, we found the best fit to Pareto optimality when individuals were plotted in the trait-space of time preferences for reward, evaluated with the Delay Discounting Task (DDT). The DDT measures subjects' preference in choosing either immediate smaller rewards or delayed larger rewards. Time preference for reward was described by a triangular distribution in which each of the three vertices included individuals who used a particular strategy to discount reward. These archetypes accounted for variability on many cognitive, personality, and socioeconomic status variables, as well as differences in brain structure and functional connectivity, with only a weak influence of genetics. In summary, time preference for reward reflects a core variable that biases human phenotypes via natural and cultural selection. •According to Pareto optimality theory, evolution forces trade-offs of functions.•We found that trade-offs in human behavior are related to delay discounting task.•Three reward-related strategies (archetypes) explain variability in all human domains.•A different brain structure and functional connectivity defines each strategy.•Stronger connection between PFC and reward related regions qualifies self-control.